Carbon Nanodots from Olive Solid Wastes for Photodegradation of Methylene Blue - Azzam, Halah; Dweikat, Hanan; Anaya, Kayan; Bin Ali, Rasha (My University, 2021)
The project talks about the topic of carbon dots as they are emerging materials in nanotechnology as attractive photocatalysts, due to their high water solubility, good chemicals and photo-endurance, tunable photoluminescence and optical phenomena. Colloidal quantum blobs were synthesized from solid olive waste by pyrolysis of the waste at 600 °C followed by chemical oxidation in the presence of hydrogen peroxide. The colloidal quantum blobs synthesized in this work were used as a photocatalyst for the photolysis of methylene blue under different conditions, such as; Catalyst concentration, pollutant solution pH (M.B), salt content, light source distance, light source and pollutant concentration (M.B). The lysis efficiency and rate of all the above factors were studied, and it was found that the increase in the dose of colloidal quantum drips in M.B solution linearly increases the efficiency and rate. On the other hand, the maximum degradation rate was observed at pH = 10.6 with an efficiency of 92% after 120 min of irradiation. Furthermore, the presence of NaCl in the contaminant solution negatively affects the decomposition coefficients showing a slight decrease in the decomposition rate, with each addition of 2 mg reducing the rate by less than 1.2-fold. The potential and distance of the visible light source from the contaminated cell have an obvious effect on degradation, increasing the light power from 10 to 50 W, and increasing the degradation rate by 16 times. Besides using colloidal quantum dots as photocatalysts in solutions, the colloidal quantum dots/ZnO nanocomposite was prepared, and the photolysis of M.B was also tested with showing improvement due to the addition of colloidal quantum dots. For example, the decomposition rate has been increased by two times.